Influence of geological structures on the occurrence of coalbed methane in Sima coal mine, China - Liu, Hongyang; Zhang, Boyang; Li, Xuelong; Liu, Chengwei; Wang, Chen; Wang, Feng; Cui, Zhenhua; Chen, Deyou (Frontiers in Earth Science, 2022)
Geological structures of Sima coal mine in Shanxi Province were analyzed to understand the control effect of the geological structures on the occurrence of coalbed methane (CBM) in coal seam #3 of Sima coal mine. The CBM contents in the districts #2 and #3 of Sima coal mine were tested, and the effects of buried depth, fault and collapse column on the distribution of coalbed methane content are studied. The research results showed that: 1) The average content of CBM has a linear relationship with buried depth and overburden thickness, but in the smallscale range of buried depth, the dispersion between CBM and buried depth is very large. 2) Faults and collapse columns significantly affect the content of local CBM nearby, but from the largescale range such as the whole mining area, the average value of CBM content at a certain buried depth will not be affected by faults and collapse columns. 3) In the hanging wall of F29 normal fault, it is roughly estimated that the average escape rate of CBM near the fault is 13.9%, while in the footwall of F29 normal fault, this value is 0.7~1.1%. The results show that there is a significant difference in the influence of the fault on the CBM content in the hanging wall and footwall. 4) The control effect of collapse column on CBM occurrence is related to the development height of collapse column, the cementation degree of collapse column, groundwater runoff conditions and other factors. It can be divided into three categories: aggregation action, escape action (such as collapse column X8) and no obvious effect (such as collapse column DX7).